2015
DOI: 10.1159/000371847
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Sleep Duration with Obesity and Sarcopenia in Community-Dwelling Older Adults

Abstract: Background: Numerous studies have reported the relationship between sleep duration and obesity in elderly adults; however, little is known about the relationship of sleep duration and sarcopenia. Objective: We examined the relationship of sleep duration with obesity and sarcopenia in community-dwelling older adults. Methods: A total of 488 community-dwelling adults (224 men and 264 women) aged ≥65 years were included in the analysis. Self-reported sleep duration and anthropometric data were collected. Skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
67
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 45 publications
11
67
2
Order By: Relevance
“…28 Chien et al demonstrated a U-shape association between sleep duration and sarcopenia. Specifically, the authors emphasized that those who had ≥ 8 hours of sleep tended to exhibit sarcopenia (OR [95% CI] = 1.89 [1.01-3.54]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Chien et al demonstrated a U-shape association between sleep duration and sarcopenia. Specifically, the authors emphasized that those who had ≥ 8 hours of sleep tended to exhibit sarcopenia (OR [95% CI] = 1.89 [1.01-3.54]).…”
Section: Discussionmentioning
confidence: 99%
“…41 Other studies have reported that both short and long sleep durations are related to sarcopenia in older females. 28 Further prospective studies are required to clarify the relationship between sleep duration and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with a recent study conducted in Taiwan. [18] In their study, Chien and colleagues recruited 488 community-dwelling older adults and also found a U-shape pattern between sleep duration and sarcopenia. However, they defined sarcopenia only based on low muscle mass which was measured by bioelectrical impedance analysis (BIA).…”
Section: Discussionmentioning
confidence: 99%
“…[18] Another study also demonstrated that postmenopausal women with long sleep durations were at risk of reduced skeletal muscle. [5] Long sleep duration has also been proven to be related to other adverse health outcomes (e.g., frailty and death).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation